Contrasting distributions and expression characteristics of transcribing repeats in Setaria viridis - Franco, Ana Luiza; Gu, Wenjia; Novák, Petr; Leitch, Ilia J; Viccini, Lyderson F; Leitch, Andrew R (The plant genome, 2025)
Repetitive DNA contributes significantly to plant genome size, adaptation, and evolution. However, little is understood about the transcription of repeats. This is addressed here in the plant green foxtail millet (Setaria viridis). First, we used RepeatExplorer2 to calculate the genome proportion (GP) of all repeat types and compared the GP of long terminal repeat (LTR) retroelements against annotated complete and incomplete LTR retroelements (Ty1/copia and Ty3/gypsy) identified by DANTE in a whole genome assembly. We show that DANTE-identified LTR retroelements can comprise ∼0.75% of the inflorescence poly-A transcriptome and ∼0.24% of the stem ribo-depleted transcriptome. In the RNA libraries from inflorescence tissue, both LTR retroelements and DNA transposons identified by RepeatExplorer2 were highly abundant, where they may be taking advantage of the reduced epigenetic silencing in the germ line to amplify. Typically, there was a higher representation of DANTE-identified LTR retroelements in the transcriptome than RepeatExplorer2-identified LTR retroelements, potentially reflecting the transcription of elements that have insufficient genomic copy numbers to be detected by RepeatExplorer2. In contrast, for ribo-depleted libraries of stem tissues, the reverse was observed, with a higher transcriptome representation of RepeatExplorer2-identified LTR retroelements. For RepeatExplorer2-identified repeats, we show that the GP of most Ty1/copia and Ty3/gypsy families were positively correlated with their transcript proportion. In addition, guanine- and cytosine-rich repeats with high sequence similarity were also the most abundant in the transcriptome, and these likely represent young elements that are most capable of amplification due to their ability to evade epigenetic silencing.
Keywords: Setaria (rostlina); koncové repetice; Transcription, Genetic; transkriptom; Setaria Plant; genetická transkripce; Retroelements; Terminal Repeat Sequences; Transcriptome; retroelementy; genom rostlinný; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Genome, Plant